Hubungan Ketebalan Media Saringan Pasir Cepat dengan Efisiensi Penurunan Kekeruhan - Taty Alfiah; Berlinda Putri Winata; Ro'du Dhuha Afrianisa (Teknik Lingkungan, Institut Teknologi Adhi Tama Surabaya, 2025)
The Water Treatment Plant (WTP) Ngagel 1 built in 1922 and is still in operation today. There are six rapid sand filter units, namely filters A, B, C, D, E, and F. Each filter unit consists of 32 rapid sand filter beds. The problem faced by the rapid sand filter unit is the reduction in the thickness of the silica sand media. Therefore, this field study aims to determine the correlation between the thickness of the silica sand media and the efficiency of turbidity reduction. This study is a field study, where data collection was carried out at the WTP Ngagel 1 rapid sand filter building unit. Water samples were taken from each rapid sand filter grid in the Rapid Sand Filter buildings A, B, C, D, E, and F. The height of the silica sand media was measured in each rapid sand filter grid. Water samples were taken at the inlet and outlet of each rapid sand filter section to measure turbidity in the laboratory. This field study concluded that the efficiency of turbidity reduction by rapid sand filters is influenced by the thickness of the silica sand media, with an average correlation value of 0.72 for the six rapid sand filter units.Keywords: media thickness, rapid sand filter, silica sand, turbidity